182k views
20 votes
Photo attached Thank you

Photo attached Thank you-example-1
User Denza
by
5.4k points

1 Answer

8 votes


f'(x) = (7x^(2) - 3x + 2)^{ (7)/(2)} (14x - 3)

Step-by-step explanation

Formula :


\boxed{f(x) = u^(n) \: \rightarrow \: f'(x) = n * u^(n - 1) * u'}

Step by step :


\begin{aligned}f(x)&=(7x^(2) - 3x + 2)^{(9)/(2)}\\f'(x)&= (9)/(2)(7x^(2) - 3x + 2)^{ (9 - 2)/(2)} (14x - 3) \\& = (9)/(2) (7x^(2) - 3x + 2)^{ (7)/(2)} (14x - 3)\end{aligned}

User LexLythius
by
5.7k points